The Use of Pedicled Perforator Flaps in Chest Reconstruction: A Systematic Review of Outcomes and Reliability. Issue 4 (October 2018) - Florczak, Anne-Sophie; Chaput, Benoit; Herlin, Christian; Rousseau, Pascal; Watier, Eric; Bertheuil, Nicolas
Abstract : Background: In recent years, pedicled perforator flaps have revolutionized plastic surgery by reducing donor site morbidity and ensuring larger and deeper reconstructions with local pedicled cutaneous flaps. The aim of the study was to make a systematic review of perforator pedicled propeller flaps (PPPFs) in chest reconstruction. Methods: Pubmed and Cochrane databases were searched from 1989 to October 2016 for articles describing the use of PPPFs in chest reconstruction. The preferred reporting items for systematic reviews and meta analyses statement was used in the selection process. The review was registered on international prospective register of systematic reviews. Furthermore, operative technique, indications and complications were searched. Results: Twenty-four articles were selected (174 patients and 182 flaps). Oncological surgery was the first etiology (34.5%), followed by infections (11.5%), chest keloid scars (6.23%), malformations (4.6%), burns (3.4%), chronic ulcers (2.3%), Verneuil disease (1.8%), and acute wounds (1.8%). The arc of rotation was between 90° and 120° in 24.2%. The mean surface of flaps was 127.45 ± 123.11 cm 2 . Dissection was subfascial in 78.5% of the cases. Complications were found in 9.9% of patients and included mainly wound dehiscence (4.4%) and hematoma/seroma (2.2%). One case of total necrosis (0.5%) and 2 cases of partial necrosis (1.1%) were found. Conclusions: The possibility of numerous pedicles makes it possible for PPPFs to offset most areas of wall chest defects. Furthermore, this surgical technique is reliable and reproducible, with lower donor site morbidity than that in the case of muscular flaps, which are classically used in this location.